Wound care essentials : practice principles - Baranoski, Sharon (Wolters Kluwer, 2020)
"A crucial guide for all skin and wound care professionals, this essential resource provides authoritative science and practical instruction on wound care best practices. This must-have guide offers the latest, skin and wound care research-backed insights on prevention and management strategies. Three new chapters - Skin, Challenging Skin Conditions and Lymphedema. Skin and wound care concepts - every chapter has been updated with the most current international guidelines especially for pressure injuries and skin tears." -- Publisher.